Good to great and the social sectors : [why business thinking is not the answer : a monograph to accompany Good to great]. - Collins, James C. (James Charles), 1958- ([s.l], 2005)
Answers to commonly asked questions about how good-to-great principles can help social sector organizations make the leap to greatness, using interviews with over 100 social sector leaders.
Keywords: Leadership; Executive ability; Strategic planning; Organizational change; Technological innovations -- Management